Tumor-Resident T Cells, Associated With Tertiary Lymphoid Structure Maturity, Improve Survival in Patients With Stage III Lung Adenocarcinoma - Zhao, Hua; Wang, Hao; Zhao, Yu; Sun, Qian; Ren, Xiubao (Frontiers in Immunology, 2022)
Tertiary lymphoid structure (TLS) and tumor-resident memory T cells (TRM) play crucial roles in the anti-tumor immune response, facilitating a good prognosis in patients with cancer. However, there have been no reports on the relationship between TRM and TLS maturity. In this study, we detected TRM and the maturity of TLS by immunofluorescence staining and analyzed the relationship between their distribution and proportion in patients with lung adenocarcinoma (LUAD). The proportion of TRM within TLSs was significantly higher than that outside and was positively correlated with the survival of patients. In addition, the proportions of CD4+CD103+ TRM and CD8+CD103+ TRM were significantly increased with the gradually maturation of TLSs. We divided the patients into three levels (grade 1, grade 2, and grade 3) according to the presence of increasing maturation of TLSs. The proportion of CD103+ TRM in grade 3 patients was significantly higher than that in grade 1 and grade 2 patients, suggesting a close relationship between CD103+ TRM and TLS maturity. Furthermore, positive prognosis was associated with grade 3 patients that exhibited CD103+TRMHigh phenotype.